A survey to assess community pharmacists’ knowledge, attitudes and practices about adverse drug reaction (ADR) reporting in Malaysia / Rosdi Md Zin - Md Zin, Rosdi (2016)
Introduction: Spontaneous report of Adverse Drug Reactions (ADR) required initiative as well as motivations from healthcare practitioners to submit a report. Report published by National Pharmaceutical Control Bureau (NPCB) indicated that despite increment in number of reports from healthcare practitioners, community pharmacists contributed very little to the increment. Therefore, this study aimed to provide basic information with regards to submissions of ADR reports by the pharmacists in retails. Objectives: To describe knowledge, atitude, practices, barriers as well as factors contributed to submission of ADR reports. Method: A crosssectional face-to-face distributions of questionnaires was conducted in the state of Selangor involved 278 phamacists to study the knowledge, attitude and practices among community pharmacists in term of ADR reporting. Pharmacists involved were selected by using combination of cluster and convenience sampling. Districts involved were selected by using cluster sampling while individual pharmacists was selected based on convenience sampling. Data gathered were analyzed by using descriptive statistics in the form of frequency and percentages. Results: A total of 278 questionnaires were distributed but only 219 pharmacists responded (response rate of 78.8%). Pharmacists were evenly distributed regarding involvement in pharmacovigilance courses though 26.0% were not aware of the presence of pharmacovigilance center in Malaysia. MADRAC (75.8%) were considered as the method to report ADR among community pharmacists, though upon encountering one, pharmacists preferred to ask patients to contact physician regarding their ADR problems. Among the top reasons for not reporting ADR were lack of informations from patients (84%), uncertain associations between the reactions and the drugs (72.2%), insufficient clinical knowledge (64.9%), unavailability of ADR reporting form (49.3%) as well as unaware of the necessity to report ADR (48%). Conclusions: The study provided general information regarding pharmacists’ knowledge, attitude and practices about ADR reporting which the national authorities could venture and act upon to draft strategies and methods to further increase ADR reports from the retail pharmacists. Based on the study, pharmacists have a good knowledge and awareness regarding national ADR reporting systems. However, attitude and practices among community pharmacists provided rooms for improvements in ADR reporting